Changes in vitamin D binding protein and vitamin D concentrations associated with liver transplantation - Reese, Peter P. (Liver Int, 2011)
BACKGROUND: Vitamin D deficiency is associated with fractures, infections and death. Liver disease impairs vitamin D and vitamin D binding protein (DBP) metabolism. AIMS: We aimed to determine the impact of liver transplantation on vitamin D, particularly on DBP and free vitamin D concentrations. METHODS: Serum 25(OH)D, 1,25(OH)(2)D and DBP concentrations were measured in 202 adults before liver transplantation and 3 months later in 155. Free vitamin D concentrations were estimated from these values. Risk factors for 25(OH)D deficiency (<20 ng/ml) and low 1,25(OH)(2)D (<20 pg/ml) were examined with logistic regression, and changes in concentrations following transplantation with linear regression. RESULTS: Pretransplant, 84% were 25(OH)D deficient, 13% had 25(OH)D concentrations <2.5 ng/ml, and 77% had low 1,25(OH)(2)D. Model for end-stage liver disease score ≥ 20 (P < 0.005) and hypoalbuminemia (P < 0.005) were associated with low 25(OH)D and 1,25(OH)(2)D concentrations. Following transplantation, 25(OH)D concentrations increased a median of 17.8 ng/ml (P < 0.001). Albumin increased from a median of 2.7 to 3.8 g/dl (P < 0.001) and DBP from 8.6 to 23.8 mg/dl (P < 0.001). Changes in total 25(OH)D were positively and independently associated with changes in DBP (P < 0.05) and albumin (P < 0.001). Free 25(OH)D concentrations rose from 6.0 to 9.7 pg/ml (P < 0.001). In contrast, total 1,25(OH)(2) Dconcentrations rose only by 4.3 pg/ml (P < 0.001) and free 1,25(OH)(2) Dconcentrations declined (P < 0.001). CONCLUSIONS: Serum total and free 25(OH)D and DBP concentrations rose substantially following transplantation, while 1,25(OH)(2)D concentrations showed modest changes and free 1,25(OH)(2)D decreased. Studies of the effects of vitamin D status on diverse transplant complications are needed.